Design of a heuristic for balancing a multi-stage production flow line - Kays, H. M. E.; Karim, A. N. M.; Tajudin, M. N. B.; Abdesselam, M. (Trans Tech Publications, Switzerland, 2015)
A production flow line balancing problem for automotive industry has been studied. A batch of an end item is produced by transforming sheet metals into parts at different manufacturing stages followed by assembly operations. The forming operations of the sheet metals into various parts and their assembly works are illustrated through 22 different tasks. Some of the tasks have the processing times greater than the takt time and are categorized as extra-long tasks. Attempts were made to solve this intricate line balancing problem by adopting the Ranked Positional Weight (RPW) method. But the solution given by the RPW model loses its exactitude due to the presence of the extra-long tasks. In this research a heuristic approach based on RPW is developed through which the problem has been resolved in an efficient and effective manner and hence the proposed heuristic is deemed to be capable of balancing production lines having such extra-long tasks.